Effect of 6. Grade Turkish textbook in vocabulary development [Kelime daǧarcıǧını geliştirmede 6. Sınıf Türkçe ders kitabının etkisi] - (:unkn) unknown (Ankara University, 2013)
Vocabulary is an important communicative tool to learn and transfer the knowledge. The efficiency of this tool increases with differences in terms of content and thus, with numerousness in terms of amount. In education the most frequently used source to develop vocabulary is the textbook. Each textbook has a vocabulary of its own. It is observed that researches about vocabulary are intended to determine the number and type of words. In this research, it is tried to determine the words in Turkish textbook for sixth graders not only in terms of the number of words, but also students' degree of perception those words, which builds up the principal aim of the research. Thus, this research provides a base for forming up a list of words to be gained by the students according to their levels. As a result of the research, it is determined by the negotiation of the researcher and two teachers that students may not know only 119 out of 2203 words which are present in the Turkish textbook. Moreover, it is seen that students could know only 27 out of the words which are considered as not known by the students.
Keywords: Turkish education; Turkish textbook; Vocabulary